Tìm x
a) | x - 3 | - 3x = 7
b) | 5 + x | + 3x = 17
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(-4x+5+2x-1=3\Leftrightarrow-2x=-1\Leftrightarrow x=\dfrac{1}{2}\)
b, \(-2x+2=2\Leftrightarrow x=0\)
c, \(-2x-6=-8\Leftrightarrow x=1\)
a: =>x^2-25-x^2-3x=10
=>-3x=35
=>x=-35/3
b: =>4x^2-9-4(x^2+4x+4)=5
=>4x^2-9-4x^2-16x-16-5=0
=>-16x-30=0
=>x=-15/8
c: =>9x^2+45x-9x^2+4=7
=>45x=3
=>x=1/15
d: =>x^3+3x^2+3x+1-x^3-3x^2+5x=8
=>8x=7
=>x=7/8
a: 12:x=144
=>\(x=\dfrac{12}{144}\)
=>\(x=\dfrac{1}{12}\)
b: \(x-17=\left(-2\right)\cdot27\)
=>\(x-17=-54\)
=>\(x=-54+17=-37\)
c: \(3x-125=145\)
=>\(3x=125+145=270\)
=>\(x=\dfrac{270}{3}=90\)
\(a,12:x=144\\ x=\dfrac{12}{144}=\dfrac{1}{12}\\ ---\\ b,x-17=\left(-2\right).27\\ x-17=-54\\ x=-54+17=-37\\ ----\\ 3x-125=145\\ 3x=145+125=270\\ x=\dfrac{270}{3}=90\)
\(\Rightarrow x^2-16-x^2+3x=5\)
\(\Rightarrow3x=21\Rightarrow x=7\)
=> Chọn A
a) 3x(4x-3)-2x(5-6x)=0
\(\Leftrightarrow12x^2-9x-10x+12x^2=0\)
\(\Leftrightarrow24x^2-19x=0\)
\(\Leftrightarrow x\left(24x-19\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\24x-19=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\24x=19\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{19}{24}\end{matrix}\right.\)
Vậy x=0 hoặc x=\(\dfrac{19}{24}\)
\(a,=3x-9-4x+12=-x+3=0\)
\(\Leftrightarrow x=3\)
Vậy ..
\(b,=\left(x+2\right)\left(x+2-x+2\right)=4\left(x+2\right)=0\)
\(\Leftrightarrow x+2=0\)
\(\Leftrightarrow x=-2\)
Vậy ..
\(c,=x^3-3x^2+3x-1=\left(x-1\right)^3=0\)
\(\Leftrightarrow x=1\)
Vậy ..
\(d,\Leftrightarrow x\left(x-2\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\\x=-2\end{matrix}\right.\)
Vậy ..
\(e,=\left(2x-3-5\right)\left(2x-3+5\right)=\left(2x-8\right)\left(2x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{8}{2}=4\\x=-\dfrac{2}{2}=-1\end{matrix}\right.\)
Vậy ...
a) Ta có: 3(x-3)-4x+12=0
\(\Leftrightarrow3\left(x-3\right)-4\left(x-3\right)=0\)
\(\Leftrightarrow x-3=0\)
hay x=3
Vậy: S={3}
b) Ta có: \(\left(x+2\right)^2-\left(x+2\right)\left(x-2\right)=0\)
\(\Leftrightarrow x^2+4x+4-x^2+4=0\)
\(\Leftrightarrow4x=-8\)
hay x=-2
Vậy: S={-2}
c) Ta có: \(x^3+3x=3x^2+1\)
\(\Leftrightarrow x^3-3x^2+3x-1=0\)
\(\Leftrightarrow x-1=0\)
hay x=1
Vậy: S={1}
d) Ta có: \(\dfrac{2}{3}x\left(x^2-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2-4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\\x=-2\end{matrix}\right.\)
Vậy: S={0;2;-2}
\(a,\Leftrightarrow x^2+6x+9-x^2+3x+10=1\\ \Leftrightarrow9x=-18\Leftrightarrow x=-2\\ b,\Leftrightarrow4x^2-4x+1-4x^2+17x+15=3\\ \Leftrightarrow13x=-13\Leftrightarrow x=-1\\ c,\Leftrightarrow3x\left(x-2\right)+4\left(x-2\right)=0\\ \Leftrightarrow\left(3x+4\right)\left(x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{4}{3}\\x=2\end{matrix}\right.\\ d,\Leftrightarrow2x\left(3x+5\right)-6\left(3x+5\right)=0\\ \Leftrightarrow\left(x-3\right)\left(3x+5\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{5}{3}\end{matrix}\right.\)
a) 6x(5x + 3) + 3x(1 – 10x) = 7
⇒ 30x2+18x+3x-30x2=7
⇒21x=7
⇒x=\(\dfrac{7}{21}\)
⇒x= \(\dfrac{1}{3}\)
b) (3x – 3)(5 – 21x) + (7x + 4)(9x – 5) = 44
⇒15x-63x2-15+63x + 63x2-35x+36x-20=44
⇒79x-35=44
⇒79x=44+35
⇒79x=79
⇒x=1
a) đk: \(x\ge-\frac{7}{3}\)
\(\left|x-3\right|-3x=7\)
\(\Leftrightarrow\left|x-3\right|=3x+7\)
\(\Leftrightarrow\orbr{\begin{cases}x-3=3x+7\\x-3=-3x-7\end{cases}}\Leftrightarrow\orbr{\begin{cases}2x=-10\\4x=-4\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-5\left(ktm\right)\\x=-1\left(tm\right)\end{cases}}\)
Vậy x = -1
b) đk: \(x\le\frac{17}{3}\)
\(\left|5+x\right|+3x=17\)
\(\Leftrightarrow\left|x+5\right|=17-3x\)
\(\Leftrightarrow\orbr{\begin{cases}x+5=17-3x\\x+5=3x-17\end{cases}}\Leftrightarrow\orbr{\begin{cases}4x=12\\2x=22\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\left(tm\right)\\x=11\left(ktm\right)\end{cases}}\)
Vậy x = 3
Ta có |x - 3| - 3x = 7
=> |x - 3| = 3x + 7
ĐK : \(3x+7\ge0\Rightarrow x\ge-\frac{7}{3}\)
Khi đó |x - 3| = 3x + 7
<=> \(\orbr{\begin{cases}x-3=3x+7\\x-3=-3x-7\end{cases}}\Rightarrow\orbr{\begin{cases}-2x=10\\4x=-4\end{cases}}\Rightarrow\orbr{\begin{cases}x=-5\left(\text{loại}\right)\\x=-1\left(\text{tm}\right)\end{cases}}\)
Vậy x = -1
b) Ta có |5 + x| + 3x = 17
<=> |5 + x| = 17 - 3x
ĐK \(17-3x\ge0\Rightarrow x\le\frac{17}{3}\)
Khi đó |5 + x| = 17 - 3x
<=> \(\orbr{\begin{cases}5+x=17-3x\\5+x=17+3x\end{cases}}\Rightarrow\orbr{\begin{cases}4x=22\\-2x=12\end{cases}}\Rightarrow\orbr{\begin{cases}x=5,5\left(\text{tm}\right)\\x=-6\left(\text{tm}\right)\end{cases}}\)
Vậy \(x\in\left\{5,5;6\right\}\)